The effect of plowing depth and distance between the two beds of furrows opener developed under different tillage systems on some soil physiology and sunflower crop growth - al batat, Diaa Adnan Hameed; Majed Salih Himoud (University of Thi-Qar Journal of agricultural research, 2023)
Abstract: The research was conducted in clayey loamy soil using two plowing systems (T1 chisel) and (T2 moldboard) and three depths of plowing D (10, 20, 30 cm) and three spacing between the two plates of each of the furrows opener (40, 50, 60 cm). ) to study the effect of the developed furrows opener on the physical properties of the soil (bulk density and porosity) and the growth characteristics of the sunflower crop (plant height, , productivity,) The furrows opener, when used after the moldboard plow, gave the highest height and the maximum quantity of the total seed yield of the plant, while the three mentioned traits recorded the highest increase at the maximum depth of the stalk (30 cm) and the largest spacing between the boards (60 cm) between the two plates of each of the three The furrows opener weapons, and the traits were affected (Plant height and total seed yield) were significantly affected by the bilateral and triple interactions between the study factors (tillage systems, machine depth, and the distance between the two plates) .While it affected some of the physical soil characteristics represented by the bulk density of the soil and the total porosity of the soil, the sander recorded a decrease in the apparent soil density when used after the chisel plow, and also decreased with the increase in the depth of the machine and with the increase of the inter-distance between the boards of furrow opener, while the bilateral interference was recorded between systems Tillage and tillage depth had a significant effect, while the binary interactions between (tillage regimes spacing between the boards, plow depth, and spacing between the boards) and the triple interaction between the study factors (tillage regimes, plow depth, and spacing between the boards) had no significant effect on bulk density. The developed plow excelled when used after the chisel plow by recording the highest total porosity, which increased with increasing the depth of the machine and increasing the inter-distance, while the bilateral interference between the tillage systems and the depth of the machine had a significant effect, while the bilateral interactions between (the tillage systems and the inter-distance, the depth of the machine and the inter-distance ) and the triple overlap between the study factors (tillage systems, machine depth and spacing between the boards) any significant effect on the total porosity of the soil. Keywords: plowing systems, the depth of the machine (the depth of plowing), the distance between the furrow opener plates.